Three combinations in Brazilian Plinia (Myrtaceae) - Sobral, Marcos; Mazine, Fiorella F.; Souza, Marcelo Costa (Phytotaxa, 2017)
Plinia Plumier ex Linnaeus (1753: 516; for descriptions see Landrum & Kawasaki 1997: 529 and Wilson 2011: 255) is largely identified by the presence of congested to racemiform (very rarely paniculiform) inflorescences with tetramerous, bilocular and tetraovulate flowers with calyces persisting after anthesis and seeds with two distinct plano-convex cotyledons devoid of a hypocotyl. It is an American genus with about 75 recognized species from which about 40 are known from Brazil (Govaerts et al. 2017). Along the examination of southeastern Brazilian collections we have spotted three species with morphological characters suggestive of its inclusion in Plinia, for which new combinations in this genus are herein proposed. When possible, available online type images are cited by reference to herbarium acronyms and barcode numbers (acronyms follow Thiers 2017).